Does the combination of erythropoietin and tapered oral corticosteroids improve recovery following iatrogenic nerve injury?. Issue 8 (August 2016) - Bernstein, Derek T.; Weiner, Bradley K.; Tasciotti, Ennio; Mathis, Kenneth B.
Abstract: Introduction: The reported prognosis for recovery after peripheral nerve injury is remarkably poor. Deficits may persist for years, resulting in significant functional disability. Both corticosteroids and Erythropoietin have been investigated as neuroprotective agents; however, their efficacy in total hip and knee arthroplasty is not known. The purpose of this study was to evaluate the effect of systemically-administered Erythropoietin and tapered oral corticosteroids on the recovery of postoperative nerve palsies in the setting of total hip and knee arthroplasty. Methods: Eleven patients sustaining postoperative peripheral nerve injuries after total hip or knee arthroplasty were treated acutely with Erythropoietin and tapered oral steroids. Motor and sensory function was assessed clinically pre- and postoperatively until complete motor recovery or for a minimum of 1 year. Results: Motor loss was complete in seven (64%) patients and partial in four (36%). Seven (64%) patients' symptoms affected the common peroneal nerve distribution and four (36%) had concomitant tibial nerve involvement. Eight (73%) patients experienced full motor recovery at an average of 39 days (range: 3–133 days), and three (27%) had near-complete motor recovery. At final follow up, no patient required assistive devices for ambulation. Conclusions: Administration of Erythropoietin coupled with oral tapered steroids for patients sustaining iatrogenic nerve injuries in total hip and knee arthroplasty demonstrated faster and more complete recovery of motor and sensory function compared to previous reports in the literature. This study highlights the importance of further investigation to define the role of each in the setting of acute postoperative nerve palsies. Level of evidence: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.